Ecological Factors Affecting the Human Organism Living in the Conditions of the Republic of Karakalpakstan - Kaipova, Sh.; Oralbaeva, A.; Sherniyazova, F. (American Journal of Biology and Natural Sciences, 2025)
This article discusses various living organisms inhabiting planet Earth and their interactions with each other and the environment. Special attention is given to the powerful impact of humans on nature. The article analyzes the effects of ecology on human health, focusing on the situation in the Republic of Karakalpakstan based on statistical data. Additionally, it provides an in-depth overview of atmospheric pollution and its negative impact on the human body, particularly on respiratory diseases, cardiovascular issues, and the health of mothers and children. The author also emphasizes the importance of lifestyle, environmental conditions, and medical services for health preservation, highlighting that air pollution is a global problem. The article aims to illustrate the connection between humans and the environment, the necessity of addressing ecological problems, and ensuring a healthy future.